A terawatt pulse-power generator with a microsecond plasma-opening switch; IEEE Transactions on Plasma Science; Vol. 18 , iss. 1 - Bugaev S. P.; Volkov A. M.; Iskol'dsky A. M.; Kim A. A.; Koval'chuk B. M.; Kokshenev V. A.; Mesyats G. A. Gennady Andreyevich; Novikov A. A.; Yakovlev V. P. (1990, 1990)
В фонде НТБ ТПУ отсутствует